Early-warning tools to forecast general government deficit in the euro area: the role of intra-annual fiscal indicators - Javier J. Pérez (European Central Bank (ECB), 2005)
In this paper I evaluate the usefulness of a set of fiscal indicators as early-warning-signal tools for annual General Government Net Lending developments for some EMU countries (Belgium, Germany, Spain, France, Italy, The Netherlands, Ireland, Austria, Finland) and an EMU aggregate. The indicators are mainly based on monthly and quarterly public accounts' figures. I illustrate how the dynamics of the indicators show a remarkable performance when anticipating general government accounts' movements, both in qualitative and in quantitative terms.
Keywords: C53; E6; H6; 330; European Monetary Union; Fiscal forecasting and monitoring; General Government Deficit; leading indicators; Frühwarnsystem; Haushaltsdefizit; Wirtschaftsindikator; Prognose; Eurozone; EU-Staaten; Europäischer Stabilitätsmechanismus